Disrupting the UK energy system: causes, impacts and policy implications - Ketsopoulou, I; Taylor, P; Watson, J; Brand, C; Killip, G; Et al. (UK Energy Researc Centre, 2019)
Energy systems around the world are changing fast due to rapid technical change, the need to tackle climate change and growth in demand in the developing world. The Paris Agreement and the IPCC’s 1.5 degree report have strengthened the case for rapid emissions reduction – including plans to transition to net zero energy systems and economies. A key feature of this emerging revolution is the disruption of established technologies, markets and business models.